Deception in Hitoshi One's Tokyo Swindlers A Sociology of Literature Study - nur Aini, aisyah; Seruni, Ayu Putri (Ethical Lingua: Journal of Language Teaching and Literature, 2025)
Fraud is a form of criminality that often occurs in modern society and is often raised in literary works, including films. This study aims to analyze the forms of fraud in Hitoshi One's Tokyo Swindlers and explore the three elements in Donald Cressey's Triangle Fraud theory, namely pressure, opportunity, and rationalization. The method used is descriptive qualitative with a literary sociology approach. Data were obtained through literature study and content analysis of movie scenes depicting fraudulent practices. The results showed that the movie Tokyo Swindlers represented various forms of fraud such as identity fraud, transactions, hoaxes, and money laundering, which were carried out systematically by a land mafia group. The three elements of the Fraud Triangle are found explicitly in the motivation and behavior of the characters in the film. This research shows that movies can be a powerful medium of social reflection on the reality of criminality in society. The limitation of this research lies in the focus of a single object and has not reached the audience's reception. This research is expected to contribute to literary studies, criminology, and popular culture studies.